A Comparative Study Between Organic Agriculture for Vegetables and Fruits Production in Lao PDR and the MRL Approach Used by Other Countries in the Mekong Region - Makino, Takeo; Inthalangsee, Bouthsakone (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
Food safety and the reduction of chemical use in agriculture, in particular, are common issues that reflect consumer concerns in many developing countries. This paper summarizes the history of the development of Organic Agriculture (OA) in Lao PDR, followed by the outline of the Japan International Cooperation Agency (JICA) Clean Agriculture Development Project (CADP) which supports organic vegetables and fruits production under the clean agriculture policy promoted by the Lao government. Next, the relevant policies of its neighboring countries in the Mekong region (Thailand, Vietnam, and Cambodia) are also summarized. The policies in these countries focus mainly on reducing chemical residues based on the Maximum Residue Limits (MRL) rather than promoting OA, which has recently been included in their national policies in response to social demands for chemical reduction in agriculture. Finally, the paper compares the approach of Lao PDR and other countries in the Mekong region. As a result, the Lao approach can contribute to improving both food safety and income generation of farmers. In contrast, the MRL-based approach has some limitations due to its insufficient operations under the regulatory systems in these countries. This suggests that the Lao approach should be taken into consideration by other developing economies where small-scale farmers are the majority.